Labour and the American community/by Derek C. Bok and - Bok, Derek C. (New Delhi, 1974)
IN EARLY 1966, under the auspices of the Special Studies Project of the Rockefeller Brothers Fund, we agreed to undertake this study of labor and the American community. It would have been more consonant with the traditions of the Special Studies Project to have worked toward a report to be signed by a distinguished panel of labor, management, and public representatives. After con sultation with interested parties, however, we strongly recom mended against such a procedure because the divergent views of so many participants and observers in the labor field would have made it difficult to reach agreement on any but the most general propositions. Therefore, the following book is entirely our own. In writing it, however, we have benefited, particularly in the forma tive period of our ideas, from the advice of a small advisory com mittee headed by David Rockefeller, under whose initiative the project was started. For several years, Mr. Rockefeller had been disturbed by what he saw on the labor-management scene, and it was his thought that an analysis of the internal, community, and employer relationships of the labor movement would be a valu able and timely contribution to the general understanding of the field. Other members of the advisory committee were Victor Borella, Arthur F. Burns, William F. Butler, Louis W. Cabot, Dana S. Creel, Nancy Hanks, David A. Morse, A. H. Raskin, Don ald B. Straus, David Sullivan, and Frazar B. Wilde. We are deeply grateful for their interest, suggestions, and critical comments.
Keywords: Economics